BioOncology online – a new World Wide Web-database concerning biological oncology - Mackiewicz, Małgorzata; Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 1999)
Among recently created websites concerning oncology, it is worth to visit a database „BioOncology online” at http://www.biooncology.com. It is a new www site sponsored by Gentech Inc., which is devoted to biological oncology. The creators of this website assure that the resource of information will be still developed and the „Oncology News” will be weekly updated.